Survival of Ucides cordatus (Decapoda: Ocypodidae) megalopae during transport under different conditions of density and duration - Ventura, Robson; Silva, Ubiratã A. T. da; Ostrensky, Antonio; Cottens, Kelly; Perbiche-Neves, Gilmar [UNESP] (Sociedade Brasileira de Zoologia, 2010)
Target areas for Ucides cordatus (Linnaeus, 1763) restocking programs are often located far from the laboratory where larval rearing is developed. During translocation, the larvae are submitted to highly stressful conditions due to handling, packing, and transport activities. The aim of the present study was to assess the mortality rates of U. cordatus megalopae caused by different transportation procedures. Megalopae at loading densities of 50, 150, and 300 ind.L-1 were packed in double polyethylene 12 x 25 cm plastic bags with 200 ml of marine water at salinity 30. The bags were filled with oxygen at a proportion of 1:2 parts of water and sealed tightly. The trepidations during transport were simulated by the use of a shaker device (800 vibrations/minute) over periods of three and six hours inside a dark container. The survivorship rates of larvae after simulation were compared to those obtained in control groups, which consisted of plastic vials with megalopae at a loading density of 50 ind.L-1 maintained at rest. Immediately after the two transport simulations, there was no significant difference in survivorship between the treatments and the control. However, 24 hours after simulation some of the tested densities resulted in significantly lower survivorships. The results demonstrated that U. cordatus megalopae can tolerate six hours of shaking during transportation, at high densities with minimal mortality.
Keywords: Cannibalism; larvae; mangrove crab; stress; transport